DC-to-AC Inverter Design for Photovoltaic System - Mohamed Edardar, Mohamed (1999)
With the recurrent oil crises and the new environmental boundary conditions for energy production and use, the Photovoltaic, PV, system development can be a very promising strategic solution, which realises together with the Photovoltaic energy cost effectiveness goal, an actual clean, renewable, and alternative energy option. However, the continuos decline in Photovoltaic module prices in the international market gives more attention to design the supplementary equipment with low cost and high reliability, such as DC-to-AC inverter For that reason, this project has the objective of designing and implementing a prototype DC-to-AC invel1er which used to power small houses or huts in the rural areas. The input of this inverter is four batteries of twelve volt, which would be charged by a photovoltaic solar array. The design of the solar array and its controller is not within the aim of this project. However, a theoretical study is given for the photo voltaic system in the first chapters for a purpose of illustration.The DC-to-AC invel1er is designed as a single phase bridge switched mode circuit, using power MOS FET switches and electronic components that are common and with low cost. For the sake of simplicity, a single pulse width modulation is applied which gives a reasonable efficiency with rejection of the third harmonic and its multiple. The detailed analysis of the design and experimental construction of the inverter are discussed in this report.